PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI FPB DAN KPK: (Penelitian Tindakan di SDN 1 Sukarame, Bandar Lampung) - Lesmi Atika (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
The purpose of this study was to improve the quality of mathematics learning in determining FPB and KPK through the application of the NHT type cooperative learning model to grade VI students of SDN 1 Sukarame, Sukarame District, Bandar Lampung. This type of research is a classroom action research with two cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. In each cycle, two meetings were held. The research subjects were 22 students of class VI SDN 1 Sukarame, consisting of 16 boys and 6 girls. Data collection techniques using tests, observations / observations, field notes, and documentation. The results of the research is that through the application of the Numbered Head Together (NHT) learning method in mathematics learning, the material determines FPB and KPK to improve teacher skills, student activities, and student learning outcomes of Class VI SDN Sukarame for the 2018/2019 academic year. Suggestions are given that teachers should use innovative models and varied media in learning.